2011
DOI: 10.1111/j.1743-6109.2010.02115.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Sex Hormones Play No Role in the Association Between Sexual Activity and the Risk of Prostate Cancer

Abstract: Introduction High sexual activity (SA) has been reported to reduce the risk of prostate cancer (PC). The role of sex hormones (SHs) in this regard remains controversial. Aims To determine the impact of SA and SHs on PC development. Methods In a multicentric hospital-based case–control study, 194 newly diagnosed PC patients along with 317 age-matched controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In 2004, Stattin et al conducted a case-control study of 708 men with CaP and found a modest but significant decrease in CaP risk among men with higher pretreatment testosterone levels (P=0.05) (56). Two similarly designed studies also reported that men with higher testosterone levels had a lower risk of CaP (50,51). A lower risk of biochemical recurrence and better prognosis for both localized and metastatic CaP after radical prostatectomy have also been observed in men with higher pretreatment testosterone levels (52-54).…”
Section: Methodsmentioning
confidence: 89%
“…In 2004, Stattin et al conducted a case-control study of 708 men with CaP and found a modest but significant decrease in CaP risk among men with higher pretreatment testosterone levels (P=0.05) (56). Two similarly designed studies also reported that men with higher testosterone levels had a lower risk of CaP (50,51). A lower risk of biochemical recurrence and better prognosis for both localized and metastatic CaP after radical prostatectomy have also been observed in men with higher pretreatment testosterone levels (52-54).…”
Section: Methodsmentioning
confidence: 89%
“…A lively debate on “Is testosterone a friend or foe of the prostate?” in this journal a year ago [28] combined expert opinion with a critical review of the currently available literature and found that there is no conclusive evidence that TRT “increases the risk of PCa or even prostatic hyperplasia.” Also, reassuringly, higher endogenous TT and FT, and factors known to be associated with them such as sexual activity, have been found to be protective against PCa [29].…”
Section: Discussionmentioning
confidence: 97%
“…42 These findings were supported by 2 subsequent prospective studies of 65 and 194 men that demonstrated a protective effect of higher total testosterone levels against prostate cancer. 4344 A prospective cohort study of 227 patients with median follow-up of 7.7 years showed that increased pretreatment serum testosterone (>11 nmol/l) correlated with a decreased risk of biochemical recurrence after radical prostatectomy. 45 Two studies by Imamoto et al and Yamamoto et al observed that higher pretreatment testosterone levels predict a positive prognosis in patients with metastatic and localized prostate cancer.…”
Section: The Relationship Between Endogenous Testosterone Levels and mentioning
confidence: 99%